Obstacles to cross-border cooperation – Case of Croatia and Hungary - Sanja TIŠMA; Krešimir JURLIN; Helena ČERMAK (European Journal of Geography, 2018)
The focus of this paper is to identify most significant obstacles that hinder bilateral trade between Hungary and Croatia and propose solutions for improvements by using the gravity models, precisely the Newtonian model of gravitation. The results of the research show that in spite of interest for cross-border cooperation being expressed by the stakeholders from both sides of the border, Somogy County and Virovitica-Podravina County belong to less developed, deprived rural areas of Hungary and Croatia. The key weaknesses for cross-border cooperation include lack of transport connections and language barrier, while strengths reflect in entrepreneurial spirit and opportunity to apply and implement joint entrepreneurial projects financed by the European Union (EU) funds.